Geological heritage at risk in NW Spain. Quaternary deposits and landforms of “Southern Coast” (Baiona-A Garda) - Casais, Manuela Costa (2013)
Over the last decade, a knowledge base has been built up worldwide in relation to geological heritage and geodiversity, and respective working methodologies. However, the absence of knowledge and technical information by the local, regional and national authorities about geosites makes it difficult to create appropriate legislation and to assure a good management. There is also a public ignorance about geological processes and their relationship to biodiversity, as well as their value as natural heritage. This study focuses on the Autonomous Community of Galicia (NW Spain), specifically the “Southern Coast” area established in the Planning Programme for the Coast (POL) and brings to light the importance of the Quaternary deposits and associated landforms. The study concludes that the Southern Coast should be recognized as an area-type geosite. Taking into account the evaluation of their scientific value, the landforms of Oia and San Xián are proposed as geosites. Legal mechanisms of protection need to be reinforced and new, more specific ones, developed in tandem that make reference to the fact that these landforms exemplify environmental records of the past. This area is unique on a national level due to the scientific and educational value of the deposits. Therefore, they should be proposed to the Spanish Geological Survey (IGME) for inclusion in the general list of geosites of the Spanish State.